2015
DOI: 10.1080/15419061.2016.1225196
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde-derived advanced glycation end products (glycol-AGEs)-induced vascular smooth muscle cell dysfunction is regulated by the AGES-receptor (RAGE) axis in endothelium

Abstract: Advanced glycation end-products (AGEs) are involved in the development of vascular smooth muscle cell (VSMC) dysfunction and the progression of atherosclerosis. However, AGEs may indirectly affect VSMCs via AGEs-induced signal transduction between monocytes and human umbilical endothelial cells (HUVECs), rather than having a direct influence. This study was designed to elucidate the signaling pathway underlying AGEs-RAGE axis influence on VSMC dysfunction using a co-culture system with monocytes, HUVECs and VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…It has been described that AGEs can produce ROS by activating NADPH oxidases [67,68], the mitochondrial respiratory chain, microsomal enzymes, xanthine oxidase, and arachidonic acid pathways [69][70][71] by interacting with their receptor ( Figure 2). There is considerable evidence that ROS are generated upon interaction of AGEs with RAGE.…”
Section: Reactive Oxygen Species/reactive Nitrogen Species Are Intermmentioning
confidence: 99%
“…It has been described that AGEs can produce ROS by activating NADPH oxidases [67,68], the mitochondrial respiratory chain, microsomal enzymes, xanthine oxidase, and arachidonic acid pathways [69][70][71] by interacting with their receptor ( Figure 2). There is considerable evidence that ROS are generated upon interaction of AGEs with RAGE.…”
Section: Reactive Oxygen Species/reactive Nitrogen Species Are Intermmentioning
confidence: 99%
“…In particular, PM purified from P. asiatica is a phenylpropanoid glycoside that contains caffeic acid derivatives [31, 33]; nevertheless, the molecular mechanism of how PM modulates endothelial dysfunction remains uncertain. Our groups have reported that glycolaldehyde-derived AGEs stimulated intracellular ROS production and pro-inflammatory mediators including TNF-α and IL-1β via the AGE-RAGE axis [39]. One recent study showed that co-treatment with PM and glycer-AGEs in keratinocytes and fibroblasts inhibits UVB-irradiation- and AGE-induced RAGE overexpression and proinflammatory cytokine expression via attenuating MAPK activation by ROS [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that overexpression of RAGE is activated by AGEs in vascular dysfunction and resulting in apoptosis, oxidative stress and inflammation responses (35). There is a growing body of evidence that shows that AGE-RAGE interaction with a positive feedback loop is related to the dysfunction of VSMCs (10,3638). A previous study found that 100 µ g/ml AGEs enhanced vascular calcification through a RAGE/oxidative stress pathway (38).…”
Section: Discussionmentioning
confidence: 99%